2020
DOI: 10.1093/mnrasl/slaa128
|View full text |Cite
|
Sign up to set email alerts
|

What drives galaxy quenching? Resolving molecular gas and star formation in the green valley

Abstract: We study quenching in seven green valley galaxies on kpc scales by resolving their molecular gas content using 12CO(1–0) observations obtained with NOrthern Extended Millimeter Array and Atacama Large Millimeter Array, and their star formation rate using spatially resolved optical spectroscopy from the Mapping Nearby Galaxies at Apache Point Observatory survey. We perform radial stacking of both data sets to increase the sensitivity to molecular gas and star formation, thereby avoiding biases against strongly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
28
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 54 publications
19
28
1
Order By: Relevance
“…Surveys of the galaxy population at ∼ 0 additionally suggest that the offset from the SFMS is driven by a combination of (molecular) gas fraction and star formation efficiency (e.g. Zhang et al 2019;Piotrowska et al 2020;Brownson et al 2020). This is consistent with our findings in Section 3.2, where we predict that the star formation efficiency decreases steeply with * (and can thus be considered synonymous) at fixed gas fraction.…”
Section: Implications For Galaxy Evolution and Quenchingsupporting
confidence: 89%
“…Surveys of the galaxy population at ∼ 0 additionally suggest that the offset from the SFMS is driven by a combination of (molecular) gas fraction and star formation efficiency (e.g. Zhang et al 2019;Piotrowska et al 2020;Brownson et al 2020). This is consistent with our findings in Section 3.2, where we predict that the star formation efficiency decreases steeply with * (and can thus be considered synonymous) at fixed gas fraction.…”
Section: Implications For Galaxy Evolution and Quenchingsupporting
confidence: 89%
“…This case is very similar to the gas compaction and inside-out quenching episodes seen in simulations of blue nuggets (that become red nuggets) at higher redshift (Tacchella et al 2016a(Tacchella et al , 2016b. These episodes, however, need not be restricted to high-redshift, as observations with ALMA and in the MaNGA Survey (Brownson et al 2020;Lin et al 2020) have shown similar variations in central star formation efficiency sans mergers in green valley galaxies in the local universe.…”
Section: Matching Fire-cmzs With the Milky Way Cmz And External Galaxiessupporting
confidence: 74%
“…Belfiore et al (2018) find similar results with MaNGA: the SFR profiles of galaxies in the Green Valley -i.e. those located 1σ (0.39 dex) below the SFMS, experience a downward turn near the centre (see also Brownson et al 2020). Using the SIMBA cosmological simulation (Davé et al 2019), Appleby et al (2020) explain this trend as the combination of two effects: lower H 2 -gas mass presence towards smaller radii, and a decrease in SFE in that region.…”
Section: Global Sfr Enhancement Versus Radial Structurementioning
confidence: 90%